2017
DOI: 10.1039/c6sc05103k
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced electron transfer from rylenediimide radical anions and dianions to Re(bpy)(CO)3 using red and near-infrared light

Abstract: Photoinduced electron transfer dynamics are described for a set of dyads comprising rylenediimide anion chromophores and a Re(bpy)(CO)3 metal center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
82
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 39 publications
3
82
0
Order By: Relevance
“…The formation of near‐IR absorption bands of PBI .− followed by the formation of blueshifted bands of PBI 2− was reproduced on photoexcitation after purging the solution with N 2 . Thus PBI‐Bis‐2‐AN shows reversible stepwise reduction with formation of PBI .− followed by PBI 2− formation on photoirradiation [94a] . For PBI‐2‐AN and PBI‐9‐AN , however, no formation of PBI 2− was observed.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The formation of near‐IR absorption bands of PBI .− followed by the formation of blueshifted bands of PBI 2− was reproduced on photoexcitation after purging the solution with N 2 . Thus PBI‐Bis‐2‐AN shows reversible stepwise reduction with formation of PBI .− followed by PBI 2− formation on photoirradiation [94a] . For PBI‐2‐AN and PBI‐9‐AN , however, no formation of PBI 2− was observed.…”
Section: Resultsmentioning
confidence: 90%
“…Although it was reported that PBI 2− can be formed by photoexcitation of PBI .− in the presence of a sacrificial electron donor, [95] the short excited‐state lifetime of PBI .− (145±15 ps) is unfavorable for this photo‐driven intermolecular electron transfer [94a] . Majima et al.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, after UV irradiation the intensity of these peaks decreases and new absorption bands at long wavelengths (460 nm) appeared which are characteristic of naphthalenediimide radical anions (Figure b and S3 in supporting information) ,. Generally, diimide radical anions are known to have an intense band around 490 nm and weaker bands around 605 nm, 700 and 780 nm ,,. However there are reports that confirm the presence of diimide radical anion, but no peak was observed as weaker band around 605 nm, 700 and 780 nm .…”
Section: Resultsmentioning
confidence: 91%
“…Contrary, bulk metal single atoms 'conduct' electrons via LMLCT. 49,50 Such charge transfer process in Ag1@mpg-C3N4 occurs on sub ps scale, 51 while enhanced electron mobility is registered as amplified EPR signal (Table S6), enhanced fluorescence (Figure 3b) and extended lifetime of the excitons (Figure 3d).…”
Section: Resultsmentioning
confidence: 97%